Labour Market Changes, Labour Disputes and Social Cohesion in China - Cai, Fang (OECD Publishing, 2012)
Jobs are important in maintaining social cohesion. Employment provides income, but also a sense of self-worth and a meeting place for social interactions that weave the social fabric. With over 200 million unemployed globally, the number of jobs created has taken centre stage, especially in countries hit hard by the economic crisis. And yet, labour relations have become tense in many parts of the world, including those still experiencing economic growth. In 2010, China witnessed a marked increase in strikes, labour disputes and even suicides in the workplace. Understanding the economic and institutional determinants of good labour relations matters for designing and implementing better labour market policies.The increase in labour disputes in China coincided with the end of the era of surplus labour. While labour was abundant in rural hinterlands, manufacturing firms could rely on cheap labour as migrant workers would still be better off than if they stayed at home.
Keywords: Employment; Social Issues/Migration/Health; Development; China, People's Republic